To Tell the Truth: Imperfect Information and Optimal Pollution Control - Kwerel, Evan (Review of Economic Studies, 1977)
Journal Article To Tell the Truth: Imperfect Information and Optimal Pollution Control Get access Evan Kwerel Evan Kwerel Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 3, October 1977, Pages 595–601, https://doi.org/10.2307/2296911 Published: 01 October 1977 Article history Received: 01 June 1975 Accepted: 01 August 1976 Published: 01 October 1977